Side-to-Side Difference of Metatarsal Rotation in Normal Individuals. (June 2022) - Duff, Alexander; Tay, Kae Sian; Najefi, Ali-Asgar; Cullen, Nicholas; Patel, Shelain; Welck, Matthew; Malhotra, Karan
Background: A previous study defined the normal first metatarsal pronation angle (MPA) as <16 degrees and normal α angle as <18 degrees. The primary purpose of this study was to assess the side-to-side variation in first metatarsal pronation between feet in normal individuals. Methods: MPA and α angles were measured on standardized coronal weightbearing computed tomography slices. Paired t tests were used to test significance of mean side-to-side differences in a population of 63 normal, asymptomatic individuals. Results: The mean side-to-side difference in first metatarsal pronation was 4.3 degrees (95% CI 3.3, 5.2 degrees) for MPA and 4.9 degrees (95% CI 3.8, 6.0 degrees) for α angle. The normative range for side-to-side difference was calculated as 12 degrees for MPA and 14 degrees for α angle, as defined by 2 SDs from the mean. Conclusion: In a cohort of normal patients, the mean difference in first metatarsal pronation between sides was approximately 4 to 5 degrees based on MPA and α angle. However, considerable variation in differences was observed. These findings may be considered when assessing first metatarsal pronation using population-based values as it may influence thresholds for identifying pathology in an individual.